A Survey Study Evaluating and Comparing the Health Literacy Knowledge and Communication Skills Used by Nurses and Physicians - Müberra Devrim Güner MD, PhD; Perihan Elif Ekmekci MD, PhD (SAGE Publishing, 2019)
Health literacy (HL) is considered as an interaction between the demands of health systems and the skills of individuals. The current global approach demands health professionals to be more accountable for universal precautions approach and improve communication skills, and employ strategies to confirm patients' understanding. The aim of this study is to assess the knowledge and attitude of health care professionals (HCPs) about HL and their communication skills, and its effect on their practices, and to compare the findings among subgroups of HCPs. An online cross-sectional survey involving 29 items was developed for sociodemographic and professional characteristics and knowledge, attitude, and practices evaluation. Health care professionals reached by occupational organizations and social media platforms. Among the 277 participants that answered the questions, 184 were physicians and 78 were nurses, and 37.99% of physicians and 18.42% nurses heard about the term "HL" through this survey. Most of the participants stated their willingness to receive information/training on the subject and that knowing HL level would change their approach to and outcomes of the patients. Nurses were using a variety of methods that improve communication with patients and considered HCPs' lack of knowledge of the concept of "HL" and their neglect of HL as obstacles to its evaluation more than physicians. These results emphasize the urgent need of initiatives to be taken to improve the awareness of HCPs of HL and the subsequent incorporation of these initiatives into the daily health care services they provide. Nurses' awareness of HL is higher and they are already better at incorporating HL-sensitive items into their practices. Both graduate and continuing education programs need to be modified to improve HL knowledge of all HCPs and its positive effects on health care. The current structure of the roles and responsibilities of these professions needs to be improved to make it more HL sensitive.